The Effect of COVID-19 Confinement in Behavioral, Psychological, and Training Patterns of Chess Players - Fuentes-García, Juan Pedro; Martínez Patiño, María José; Villafaina, Santos; Clemente-Suárez, Vicente Javier (Frontiers in Psychology, 2020)
The outbreak of COVID-19 has triggered a pandemic, jeopardizing global health. The sports world is also suffering enormous consequences, such as the suspension of the Olympic Games in Tokyo or, in chess, the cancelation of the World Candidates Tournament 2020. Chess is a sport characterized by high psychophysiological demands derived from long training durations, tournaments, and games, leading to mental, emotional, and physical stress. These characteristics could provide chess players a certain advantage in facing quarantine situations. This study aimed to analyze the effect of COVID-19 confinement on behavioral, psychological, and training patterns of chess players based on their gender, level of education, and level of chess played. We analyzed chess players (N: 450; age = 38.12 ± 14.01 years) in countries where confinement was mandatory: Professional players (N: 55; age = 43.35 ± 13), high-performance players (N: 53; age = 38.57 ± 13.46), competitive players (N: 284; age = 36.82 ± 13.91), and amateur players (N: 58; age = 39.10 ± 14.99). Results showed that chess players significantly decreased physical activity per day while increased chess practise during the confinement period. However, anxiety levels remained moderate despite the anti-stress effects of physical activity. Amateur players showed a significantly higher level of social alarm than professional and high-performance players. Moreover, professional players showed higher values of extraversion than high-performance players and amateur players. In neuroticism, professional players showed higher values than high-performance players. In addition, the professional players showed higher scores in psychological inflexibility than competitive players. Finally, chess players with the highest academic level showed higher levels of personal concern and anxiety due to COVID-19 as well as lower psychological inflexibility compared to those with a lower academic level. In conclusion, chess players, especially those with a higher academic level, might have adapted their psychological profile to fit confinement situations and the worrying levels of physical inactivity.